Intraoperative cone beam computed tomography in the management of facial fractures - Stuck, Boris; Hülse, Carl Roland; Barth, Tilo Johannes (International journal of oral and maxillofacial surgery, 2012)
Computed tomography is currently the standard in preoperative evaluation of facial fractures, but cone beam computed tomography (CBCT) or digital volume tomography (DVT) offers potential advantages. Intraoperative imaging may facilitate adequate fracture reduction, optimising fracture repair. The aim of this article is to demonstrate the potential benefits of a new mobile CBCT system in a series of patients with complex facial fractures. Intraoperative imaging was performed with the xCAT ENT portable CBCT system. Images were provided in three planes and in a three-dimensional reconstruction. This system was used for intraoperative imaging of 46 consecutive facial trauma patients. The impact of intraoperative CBCT on the management of these cases is described and two select cases are presented to illustrate the potential benefits of this technique. Intraoperative CBCT was successfully performed in all patients and has led to immediate consequences in 12 (26%) cases. In 5 cases, fracture reduction turned out to be insufficient and was further optimized and in 5 other cases the titanium implan (orbital mesh) was not placed in the optimal position and the position was corrected. Bony fragments were detected and removed in 2 cases. Intraoperative imaging provides a number of advantages over post-therapeutic imaging in the management of facial fractures.
Gesehen am 08.10.2018